Copolymers of polyhydroxyalkanoates and polyethylene glycols: recent advancements with biological and medical significance. Issue 4 (7th October 2016) - Winnacker, Malte; Rieger, Bernhard
Abstract: Copolymers of polyhydroxyalkanoates (PHAs) and polyethylene glycols (PEGs) have gained high significance for biological and medical applications within the past few years. PHAs are natural biopolymers (hydrophobic biopolyesters), which can be produced microbially and also synthetically, and PEGs are biocompatible hydrophilic polyethers, which are frequently used in medicine to enhance the effect of bioactive compounds. Both polymers can be conjugated with a variety of other polymers, and in particular the conjugation with each other affords hydrophobic − hydrophilic PHA‐PEG copolymers with high significance as biomaterials. This paper describes selected recent developments in this field with a focus on synthetic approaches and the suitability of the resulting copolymers for applications in drug delivery and tissue engineering. © 2016 Society of Chemical Industry Abstract : Copolymers of polyhydroxyalkanoates (PHAs) and polyethylene glycols (PEGs) have high significance as biomaterials. Recent examples are discussed herein based on synthesis and applications in drug delivery and tissue engineering.